Algorithmic precision liquid dispensing (APLD) system - Low C.Y.; Chong K.H.; Johnny K.S.P.; Tiong S.K. (2023)
Liquid dispensing can be a very tough job especially when dealing with various liquids of different viscosity. Furthermore, to reach a precise result, it is very difficult to achieve. This paper presents a liquid dispensing system with real-time automatic control by using an analytical balancer reading as a feedback with additional mathematical PWM algorithm to optimize the dispensing process. Using the specifically custom build nozzle, the dispensing process can be accomplished in shorter duration together with higher accuracy and precision. 2010 IEEE.